ANALISIS STRATEGI MARKETING 7P PADA TRAVEL AGENT RINDU TANAH SUCI SURAKARTA - Yunita Primasanti (Universitas Sahid Surakarta, 2017)
Hajj and Umrah is one of the obligatory worship for every Muslim who can afford it. This obligation is the fifth pillar of Islam. Because the pilgrimage is an obligation, then if people who are unable to carry it out are sinful and if they do get rewarded. Almost every year 150,000 to 300,000 pilgrims and millions of Indonesian Umrah pilgrims meet Saudi Arabia, so Indonesia becomes a country that has received a quota of pilgrims in recent years significant, which is 10,000 each year. The implementation of Hajj and Umrah using travel services has now become the choice of many people, especially the people of Indonesia.The Miss Land Travel Travel agent was established based on the wishes of the owner who wants to serve the guests of God with the best service in the hope that it will be able to be holyBased on the SWOT analysis The strength of travel agents includes low prices with good quality, using certified experts, a strategic business position supported by a comfortable atmosphere. While the weaknesses of this business are insufficient human resources, lack of product variants and collaboration with other parties, especially representatives abroad. .Rindu Tanah Suci travel agent after being analyzed by the BCG Boston Consulting Group) method, including being in the position of question mark, products and business is growing but the position of products and business in competition is very high. As for its strategic planning, Rindu Tanah Suci travel agent is engaged in services, the travel agent offers a partnership program for pilgrims who want to open the business.",